Synthetic curcumin derivative DK1 possessed G2/M arrest and induced apoptosis through accumulation of intracellular ROS in MCF-7 breast cancer cells - Mohd Ali, Norlaily; Swee, Keong Yeap; Abu, Nadiah; Kian, Lam Lim; Ky, Huynh; Pauzi, Ahmad Zaim Mat; Wan, Yong Ho; Sheau, Wei Tan; Alan‑Ong, Han Kiat; Zareen, Seema; Alitheen, Noorjahan Banu; Akhtar, M. Nadeem (BioMed Central, 2017)
Aims: Curcumin is a lead compound of the rhizomes of Curcuma longa and possess a broad range of pharmacological activities. Chemically, curcumin is 1,3-dicarbonyl class of compound, which exhibits keto-enol tautomerism. Despite of its strong biological properties, curcumin has yet been recommended as a therapeutic agent because of its poor bioavailability. Main methods: A curcumin derivative (Z)-3-hydroxy-1-(2-hydroxyphenyl)-3-phenylprop-2-en-1-one (DK1) was synthesized and its cytotoxicity was tested on breast cancer cell MCF-7 and normal cell MCF-10A using MTT assay. Meanwhile, cell cycle regulation and apoptosis on MCF-7 cell were evaluated using flow cytometry. Regulation of cell cycle and apoptosis related genes expression was investigated by quantitative real time polymerase chain reaction (qRT-PCR), western blot and caspases activity analyses. Activation of oxidative stress on MCF-7 were evaluated by measuring ROS and GSH levels. Key findings: DK1 was found to possess selective cytotoxicity on breast cancer MCF-7 cell than normal MCF-10A cell. Flow cytometry cell cycle and AnnexinV/PI analyses reported that DK1 effectively arrested MCF-7 at G2/M phase and induced apoptosis after 72 h of incubation than curcumin. Upregulation of p53, p21 and downregulation of PLK-1 subsequently promote phosphorylation of CDC2 which were found contributed to the arrest of G2/M phase. Moreover, increased of reactive oxygen species and reduced of antioxidant glutathione level correlate with apoptosis observed with raised of cytochrome c and active caspase 9. Significance: DK1 was found to be more effective in inducing cell cycle arrest and apoptosis against MCF-7 cell with much higher selectivity index of MCF-10A/MCF-7 than curcumin, which might be contributed by the overexpression of p53 protein.